TRIM59 is a key regulator of growth and migration inrenal cell carcinoma - Hu, S-H.; Zhao, M-J.; Wang, W-X.; Xu, C-W.; Wang, G-D. (Cellular and Molecular Biology, 2017)
Renal cell carcinoma (RCC) is the most common renal neoplasms and metastatic is common. Previous data have shown that the tripartite motif (TRIM) family proteinswere implicated in human tumoriogenesis. In this study, we aimed to investigate the role of TRIM59 in the cell growth and migration in RCC. The expression of TRIM59 in human RCC tissues was initially examined by qRT-PCR. Alentivirus-based shRNA against TRIM59 (Lv-shTRIM59) was constructed. The effects of TRIM59 knockdown on cell proliferation were examined by in vitro MTT assay, colony formation assay and in vivo a mouse xenograft model of RCC. Cell migration and invasion after knockdown of TRIM59 were also examined by transwell assay. Our data showed that the mRNA level of TRIM59 in cancerous tissues was 2-fold increased as compared with non-cancerous tissues. Knockdown of TRIM59 in a RCC cell line 786-O significantly slowed down cell proliferative rate and decreased both the colony number and sizes. In the mouse model, knockdown of TRIM59 consistently inhibited tumor growth in vivo. Moreover, it was shown that cell migration and invasion were suppressed by 68% and 50%, respectively in TRIM59-depleted 786-O cells. Our data suggest that TRIM59 may serve as a pro-oncogenic protein in promoting the progression of RCC. Knockdown of TRIM59 may be a promising strategy concerning the early detection and treatment of RCC.